2019
DOI: 10.1001/jamaneurol.2019.2244
|View full text |Cite
|
Sign up to set email alerts
|

Association of White Matter Rarefaction, Arteriolosclerosis, and Tau With Dementia in Chronic Traumatic Encephalopathy

Abstract: IMPORTANCE Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease associated with repetitive head impacts, including those from US football, that presents with cognitive and neuropsychiatric disturbances that can progress to dementia. Pathways to dementia in CTE are unclear and likely involve tau and nontau pathologic conditions.OBJECTIVE To investigate the association of white matter rarefaction and cerebrovascular disease with dementia in deceased men older than 40 years who played football an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 66 publications
2
107
0
Order By: Relevance
“…A recent study found that moderate to severe WM rarefaction (46.6%) and arteriolosclerosis (47.2%) are common in 180 deceased football players with autopsy-confirmed CTE (Table 1). 81 Simultaneous equations regression model controlling for age and race showed more years of play corresponded to more severe WM rarefaction and greater tau pathology accumulation. Arteriolosclerosis and years of play were not related, but arteriolosclerosis was independently associated with dementia.…”
Section: Vascular Disease and White Matter Damage In Ctementioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that moderate to severe WM rarefaction (46.6%) and arteriolosclerosis (47.2%) are common in 180 deceased football players with autopsy-confirmed CTE (Table 1). 81 Simultaneous equations regression model controlling for age and race showed more years of play corresponded to more severe WM rarefaction and greater tau pathology accumulation. Arteriolosclerosis and years of play were not related, but arteriolosclerosis was independently associated with dementia.…”
Section: Vascular Disease and White Matter Damage In Ctementioning
confidence: 99%
“…Among older football players with CTE, more years of football participation corresponded to more severe WM rarefaction and greater burden of tau pathology. 81 Overall, dementia in CTE may result from multiple neuropathologies linked to RHI, including WM rarefaction and tau pathology, as well as pathologies not related to TBI or RHI, such as arteriolosclerosis and other age-related disease (►Fig. 1).…”
Section: Vascular Disease and White Matter Damage In Ctementioning
confidence: 99%
“…The hypothesis that the tau pathology may not on its own be responsible for diverse clinical symptoms reported to be associated with CTE is supported by a recent postmortem study of 180 former American football players with neuropathological diagnoses of CTE, 120 of who had dementia prior to death. 92 The authors examined dorsolateral frontal cortex (DLFC) NFT burden (a measure of CTE-related tau pathology), as well as white matter rarefaction (a marker of non-tau pathologic changes possibly associated with RHI exposure), and arteriolosclerosis (a marker of pathology not related to RHI exposure that can lead to clinical impairments). Results showed that the greater number of years of football play was associated with greater DLFC NFT burden and greater severity of white matter rarefaction but not arteriolosclerosis.…”
Section: Fluid and Neuroimaging Biomarkers For Chronic Traumatic Encementioning
confidence: 99%
“…The authors stated that these findings indicate that dementia in CTE is a result of neuropathologic changes, including p-tau and white matter rarefaction, associated with RHI exposure as well as pathologic changes, such as arteriolosclerosis, unrelated to head trauma. 92…”
Section: Fluid and Neuroimaging Biomarkers For Chronic Traumatic Encementioning
confidence: 99%
“…However, white matter atrophy, white matter rarefaction, myelin and axonal loss, astrocytic degeneration, and ptau pathology in the cortical white matter have also been described (McKee et al 2013;Holleran et al 2017;Hsu et al 2018). Furthermore, white matter rarefaction is independently associated with dementia in CTE in addition to p-tau pathology and inflammation (Alosco et al 2019;Cherry et al 2016).…”
Section: Introductionmentioning
confidence: 99%